Qualitative Study of Interpersonal Communication on Inner Child Adolescent Awareness in Sematang Borang District, Palembang City, 2022 - Chandra Satya Bintara; Didik Haryadi Santoso (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
Communication is a basic need for humans as social beings, especially teenagers in an effort to fulfill their needs. Fulfillment of communication needs on adolescent inner child awareness by using interpersonal communication. A key question arises, namely how is interpersonal communication on adolescent inner child awareness in Sematang Borang District, Palembang City in 2022? This study uses qualitative research methods with the subject of inner child adolescents. Data analysis in the research was carried out using data collection techniques by means of observation with inner child adolescent respondents in in Sematang Borang District, Palembang City through interviews. This research is qualitative using a phenomenological approach, this approach is carried out with the aim of providing a description of the existing reality.